Functionalized fiber-optic long-period grating with reduced cladding size for humidity sensing - Wei, Heming; Tan, Chee Leong; Amrithanath, Abhishek K.; Krishnaswamy, Sridhar (Society of Photo-Optical Instrumentation Engineers (SPIE), 2019)
Relative humidity (RH) is an important factor in the field of structural health monitoring, especially during the early stage of corrosion. Many methods have been proposed for humidity sensing, and one of the attractive sensors is fiber-optic long-period grating (LPG) sensors. Unfortunately, the current sensing sensitivity of this kind of sensors is limited. A thin fiber-optic LPG sensor with a self-assembled thin film of PAH+ / PAA' is proposed and demonstrated for humidity measurements. The LPG sensor is inscribed in a single-mode fiber using a CO2 laser, and the cladding size is reduced to about 27 μm. It shows that an LPG sensor with a reduced cladding size has an enhanced refractive index sensing characteristic, compared to those with normal cladding size due to the enhancement of the evanescent field. In a next step, selectivity is added to the LPG sensor coated with a film of PAH+ / PAA+ for functionalization to be sensitive to humidity. The resonance spectral responses of LPGs are experimentally investigated with respect to its sensitivity to a change in humidity that modifies the index of the nanolayer and the cladding, leading to a resonant wavelength shift. The experimental results show that the coated thin LPG has a highly sensitive resonance wavelength shift of '220.75 pm / % RH for an RH variation from 25% to 80%, of which the sensitivity is enhanced thrice compared to those with a normal cladding size. The proposed sensing setup opens LPG structures for a variety of sensing and detection applications. © 2019 Society of Photo-Optical Instrumentation Engineers (SPIE).